Impact of the flood occurrence in Kota Bharu, Kelantan using statistical analysis - Ali Khan, Mohammad Muqtada; Shaari, Nor Ashikin; Bahar, Arham Muchtar Achmad; Baten, Md Azizul (Asian Network for Scientific Information, 2014)
Over the years, flood has become one of the most destructive phenomena all over the world.It’s included Malaysia and the study area which located at the east coast of Peninsular Malaysia.Flood in Kota Bahru, Kelantan is mainly caused by heavy rainfall brought by the Northeast monsoon starting from November to March every year.It is categorized as annual flood as it occurs every year during the Monsoon season.The flood in the study area has become the most common natural hazard which caused a lot of damage for every time, during the flood event.People in the affected area had to bear with this event where they need to be evacuated and moves their private and belongings to the safe area. In this study, about 200 questionnaires were distributed to the people in the affected area after the 2010/2011 flood event. After that, the questionnaires were selected to undergo two kinds of statistical tests that were used to analyze the association of flood with the condition of flood in the study area such as frequency of flood, water depth, type of loss, total loss (in Malaysian currency, RM), health problem, electric/phone disruption and river expansion which was chi-square and bivariate correlation tests.The results of chi-square test shows that there is association between flood occurrence and the condition of flood such as frequency of flood, water depth, type of loss, average total loss, disease and psycology effect, electric/phone disruption and river expansion while the results of correlation test shows that most of the condition of flood has negative strong relationship with the flood occurrence.Overall study shows that the flood occurrences have decreased the impact of flood to the people in the affected area from years to years based on statistics of flood damage and also on victims experience.